Helicobacter pylori Infection: Clinical, Endoscopic, and Histological Findings in Lebanese Pediatric Patients - F. AL Kirdy; M. Rajab; N. El-Rifai (International Journal of Pediatrics)
Background. Helicobacter pylori (H. pylori) is a common and universally distributed bacterial infection. However, in children, active gastritis and ulcer are rarely seen. Objectives. The aims of this study were to establish the prevalence of H. pylori infection and to compare the clinical, endoscopic, and histopathological findings between infected and noninfected pediatric patients at Makassed General Hospital. Methods. Patients aged between 1 month and 17 years who underwent upper gastrointestinal endoscopy from January 2011 to January 2017 were included. The diagnosis of H. pylori was confirmed by a CLO test and/or its presence on biopsy specimens. Demographic data, clinical characteristics, endoscopic and histopathological findings, and gastritis score were recorded retrospectively. Results. During the study period, 651 children underwent upper gastrointestinal endoscopy. The main indication was abdominal pain (61%). The prevalence of H. pylori infection was 16.5%. The infection was most commonly seen among children aged between 6 and 10 years (43%). A large number of family members were associated with increased risk of infection (4.8±1.5 versus 5.2±1.8; p<0.05). Epigastric pain was more associated with H. pylori (61.3% versus 14.6% in noninfected patients; p<0.05). Nodular gastritis was commonly seen in infected patients (41.5% vs. 7.9%; p<0.05). Mild and moderate gastritis was seen more in infected versus noninfected patients (mild: 53.8% vs. 14%; moderate: 27.4% vs. 2.4%, respectively). Conclusion. Although epigastric pain was associated with H. pylori, other diagnoses should be considered since the infection are rarely symptomatic in children. Antral nodularity was associated with H. pylori infection; however, its absence does not preclude the diagnosis.